2013
DOI: 10.1002/app.39256
|View full text |Cite
|
Sign up to set email alerts
|

Shear strain and microscopic characterization of a bamboo bonding interface with poly(vinyl alcohol) modified phenol–formaldehyde resin

Abstract: The study of the shear strain distribution at the bonding interface helped us to understand the bamboo bonding interface response mechanisms to solve problems of ply bamboo deformation or bonding failure. The shear strain distribution across a twoply bamboo sheet bonded with a ductile phenol-formaldehyde resin (PF) modified by poly(vinyl alcohol) (PVA) was measured by means of electronic speckle pattern interferometry, along with tensile strength measurements to prove the shear stain distribution on a macrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Figure 5 shows the distribution of the PF resin on the bonding interface of the scrimbers. The average penetration depth (AP) and the effective penetration depth (EP) are two important indexes to assess the permeability of the adhesive at the wood bonding interface (Guan et al 2013;Qin et al 2015). Meanwhile, the average glueline thickness was also measured in this study.…”
Section: Fluorescent Characterization Of Ffpv Scrimbers Bonding Inter...mentioning
confidence: 99%
“…Figure 5 shows the distribution of the PF resin on the bonding interface of the scrimbers. The average penetration depth (AP) and the effective penetration depth (EP) are two important indexes to assess the permeability of the adhesive at the wood bonding interface (Guan et al 2013;Qin et al 2015). Meanwhile, the average glueline thickness was also measured in this study.…”
Section: Fluorescent Characterization Of Ffpv Scrimbers Bonding Inter...mentioning
confidence: 99%
“…On the other hand, bamboo is innately lacking in transverse structure like wood rays, which is not conductive to the flow of adhesives in bamboo. Guan et al characterized the penetration depth of PF resins and poly(vinyl alcohol) modified PF resins in bamboo by using fluorescence microscopy [9]. However, this observation remained at the cellular level.…”
Section: Introductionmentioning
confidence: 99%
“…To facilitate adequate mechanical interlocking, the adhesive must penetrate the wood before it is cured. Traditional wood plastic composites take wood powders or fibers as raw materials, and many authors have reported results for the penetration of adhesives (Gavrilovic-Grmusa et al 2012a,b, 2016Guan et al 2013). However, in such composites the wood unit is tiny and does not have its complete structure, so it is poorly suited to research concerning the impregnation path of resins in wood (Li et al 2013;Sheshmani et al 2013;Shamsul and Srivastava 2016;Ye et al 2016).…”
Section: Introductionmentioning
confidence: 99%